2014
DOI: 10.1177/1745691614529796
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Cumulating Meta-Analysis and Replicability

Abstract: The current crisis in scientific psychology about whether our findings are irreproducible was presaged years ago by Tversky and Kahneman (1971), who noted that even sophisticated researchers believe in the fallacious Law of Small Numbers-erroneous intuitions about how imprecisely sample data reflect population phenomena. Combined with the low power of most current work, this often leads to the use of misleading criteria about whether an effect has replicated. Rosenthal (1990) suggested more appropriate criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
321
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(327 citation statements)
references
References 70 publications
5
321
0
1
Order By: Relevance
“…Following recent recommendations, we conducted an internal meta-analysis of all the data collected for this project (Braver et al, 2014;Cumming, 2014;Maner, 2014;Schimmack, 2012;Stanley & Spence, 2014). This greatly improves the power of the test of the inhibitory spillover effect and provides insights in the consistency of the results obtained across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Following recent recommendations, we conducted an internal meta-analysis of all the data collected for this project (Braver et al, 2014;Cumming, 2014;Maner, 2014;Schimmack, 2012;Stanley & Spence, 2014). This greatly improves the power of the test of the inhibitory spillover effect and provides insights in the consistency of the results obtained across studies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of abstracts is clearly insufficient to provide statistically significant results and estimates of d have a large standard error. The correct way to incorporate the results of data collected after the analysis of an initial tranche of data is via meta-analysis (Braver et al 2014). Just adding the new data to the existing data set is wrong, since it involves deciding to collect more data after looking at the results (John et al 2012).…”
Section: Phase 2 Analysismentioning
confidence: 99%
“…In light of increasing calls to move from evaluating single studies in isolation to considering the information provided by a cumulative body of research evidence (e.g., Braver, Thoemmes, & Rosenthal, 2014;Ledgerwood, 2014;Maner, 2014), we conducted two meta-analyses to quantitatively synthesize our key results and get a better estimate of the size of the effects in our two-part story about the function of group symbols: namely, (1) the effect of group symbol on perceived entitativity and (2) the effect of motivation on symbol display behaviors. Across all of our studies that tested the first effect (the six reported in the text and two additional studies mentioned in Footnote 3 and further below in the section on Boundary Conditions), we meta-analyzed nine effect sizes estimating the influence of symbols on perceived entitativity across a total of 907 participants.…”
Section: Meta-analysesmentioning
confidence: 99%